2016
DOI: 10.1080/07347332.2016.1217964
|View full text |Cite
|
Sign up to set email alerts
|

Storytelling as part of cancer rehabilitation to support cancer patients and their relatives

Abstract: Previous research on psychosocial support for cancer-related concerns has primarily focused on either patients or their relatives, although limited research is available on how patients and their relatives can be supported together. The aim of this article is to explore the use of storytelling as a part of a residential cancer rehabilitation intervention for patients together with their relatives, with a specific focus on their management of cancer-related concerns. Ten pairs participated in the intervention a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…This sub-theme identified the importance of the opportunity to express suffering and the ability for each participant to consider and offer true and experienced feelings associated with the illness. Six [14] Individuals had an opportunity to discuss fears and worries which were aspects of the situation that were exclusive to the group [15] [24] [26] [28]. The group environment represented a space where judgement from others about individual's story/ies was suspended or limited [15].…”
Section: Subtheme A: the Expressions Of Emotions Which Validated Suffmentioning
confidence: 99%
See 4 more Smart Citations
“…This sub-theme identified the importance of the opportunity to express suffering and the ability for each participant to consider and offer true and experienced feelings associated with the illness. Six [14] Individuals had an opportunity to discuss fears and worries which were aspects of the situation that were exclusive to the group [15] [24] [26] [28]. The group environment represented a space where judgement from others about individual's story/ies was suspended or limited [15].…”
Section: Subtheme A: the Expressions Of Emotions Which Validated Suffmentioning
confidence: 99%
“…This sub-theme identified that in the process of storytelling individuals were able to describe and understand how to manage their condition because the information was shared by others enabling reflection. Four [14] [29]. One study [29] quantified this by scoring agreement with the statements out of a complete agreement of 4.…”
Section: Sub-theme (B) Developing a Shared Understanding Of Copingmentioning
confidence: 99%
See 3 more Smart Citations